Meningkatkan Kemampuan Berpikir Analisis Peserta Didik Menggunakan Model Cooperative Learning Tipe Think Talk Write - Cyntia Meilani; Erliany Syaodih; Ilyas (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
This research was conducted to obtain evidence about the application of the cooperative learning model type Think Talk Write to the improvement of students' analytical thinking skills, especially on economic subjects. The research method used is the experimental method. The research was carried out in Bandung Community Development Vocational School with a population of all students in class XI. The instrument used to obtain data on the thinking ability of students' analysis is a description test and to find out the implementation of the model of cooperative learning using Think Talk Write type using the observation sheet in the implementation of learning in the experimental class. The ability to think analysis of students was analyzed using the normality test, homogeneity test, t test, and gain test with the help of SPSS software. The data used in this study were pretest and posttest data. The results of the study of the implementation of the model of cooperative learning type Think Talk Write using the observation sheet showed very good results.